Successful Treatment of a Doberman Dog Infected with Dipylidium Caninum - Sadhu, Dasharath B; Rao, Neha; Shah, Aditya I; Patel, Om S; Raval, Sunant K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study reports a case of Dipylidium caninum infection in a dog. A four-month-old male Doberman puppy was brought to the Veterinary Clinical Complex (VCC) at Kamdhenu University, Anand with symptoms of dullness, reduced appetite, scooting behaviour and presence of whitish segments in faeces. A clinical examination revealed that the dog’s vital parameters were within the normal range, but a faecal examination detected the eggs of Dipylidium caninum. The gravid segment was examined under a microscope and confirmed the diagnosis of Dipylidium caninum, a cestode parasite. The dog was treated with an oral dose of Praziquantel at 5 mg/kg body weight and showed a complete recovery after the treatment. A follow-up faecal examination after a week was negative for any parasitic eggs or segments.
Keywords: Successful Treatment; Doberman; Dipylidium caninum